Assessment of multidrug resistant bacterial load in cosmetics bought from local markets of Bangladesh - Nusrat, Namira; Zahra, Maftuha Ahmad (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2022.